A global-local multi-scale feature extraction network for fine-grained segmentation of cyanobacterial blooms and aquatic vegetation - Yunchang Mu; Junsheng Li; Huan Zhao; Xiaodi Zhu; Zeyan Zhang; Fangfang Zhang; Shenglei Wang (Journal of Oceanology and Limnology, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

The influence mechanisms of earthworm amendment on lettuce growth and aphid suppression from the perspective of rhizosphere bacterial community - Haojun Yao; Guo Yu; Kai Zhang; Yajing Yuan; Yadong Xu; Shuyao Li; Yifeng Zhang; Chunfang Zhang (Applied Soil Ecology, 2026)

Impacts of tetracycline-lead co-contamination on soil ecosystem functions and remediation using green-synthesized iron-graphene oxide nanocomposites - Moses Akintayo Aborisade; Huazhan Long; Hongwei Rong; Fang Zhang; Akash Kumar; Andrew Ndudi Efomah; Belay Tafa Oba; Olaide Ayodele Oladeji; Oluwaseun Princess Okimiji; Francois Nkinahamira; Pamphile Ndagijimana; Ghazanfar Mehboob; et al. (Applied Soil Ecology, 2025)

Compared with plant diversity and soil fungal diversity, soil bacterial diversity drives ecosystem multifunctionality during the vegetation restoration process - Hengkang Xu; Chao Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Applied Soil Ecology, 2025)

Different responses of soil bacterial necromass carbon and fungal necromass carbon to nitrogen deposition in meadow steppe - Na Jiang; Hao Zhang; Siyu Zhang; Jie Qin; Hui Wang; Yanjun Zhang; Dianlin Yang; Lili Wang; Qiannan Yang; He Ye; Mei Hong; Haifang Zhang (Applied Soil Ecology, 2025)

Microbial phosphorus demand affects carbon-degrading potential under long-term nitrogen addition in a subtropical forest - Linna Chen; Quanxin Zeng; Qiufang Zhang; Biao Zhu; Yuexin Fan; Xiaochun Yuan; Yuehmin Chen (Applied Soil Ecology, 2025)

Inoculations of phosphorus-solubilizing bacteria alter soil properties, microbial communities, and improve crop yield and fruit quality in the tomato production system - Dan Luo; Haizhou Huang; Jianhu Wang; Tianfeng Wang; Qingfang Zhang; Yonggang Wang; Jixiang Chen (Applied Soil Ecology, 2025)

The dominance of K-strategy microbes enhances the potential of soil carbon decomposition under long-term warming - Yanli Gao; Jiacong Zhou; Teng-chiu Lin; Yiqing Li; Quanxin Zeng; Shidong Chen; Decheng Xiong; Qiufang Zhang; Zhijie Yang; Yusheng Yang (Applied Soil Ecology, 2025)

Insect residual streams supplement improves chili pepper growth: Insights into the role of rhizosphere soil microbiome and metabolome - Hanghai Zhou; Xusong Zheng; Zhigang Zhu; Qi Shen; Chenghu Yang; Lijia Jiang; Hua Li; Yuxue Liu; Xiaohong Yao; Hong Sun; Xin Wang; Chunfang Zhang; et al. (Applied Soil Ecology, 2025)

Tree mycorrhizal associations strongly mediate soil microbial β-diversity along an elevational gradient in a warm-temperate forest - Xinyue Wang; Yaru Wang; Yu Wang; Jieyan Yang; Hongyi He; Yuchen Ren; Chenlin Wang; Haibo Li; Xiongzhi Zhang; Huifang Zhang; Jingjing Wang; Xiuqing Yang; et al. (Applied Soil Ecology, 2025)

Epigenetic Resources: Gaps in Aquatic Animal Germplasm Research - Fangcheng Li; Junfang Zhang; Xiangbing Cheng; Xinyao Cui; Jiamin Sun; Qigen Liu (Reviews in Aquaculture, 2025)
Aquatic animal germplasm research plays a vital role in biodiversity conservation and sustainable aquaculture. The traditional view is that diversity of germplasm resources is commonly attributed to genetic variation. However, recent studies in transgenerational epigenetics have shown that epigenetic information can also be passed down to offspring, which is consistent with the definition of germplasm. Therefore, it is necessary to define epigenetic information, such as DNA methylation, histone modifications, and ncRNAs, which can be passed down through generations, as epigenetic resources and incorporate them into the concept of germplasm. Germplasm resources should include not only genetic resources but also epigenetic resources. Epigenetic variation can arise from genetic, environmental, or stochastic factors. Genetic and epigenetic variation co‐determine phenotypic traits. It has been demonstrated that epigenetic information can be inherited across generations in aquatic animals. DNA methylation, histone modification, and ncRNAs are involved in addressing environmental challenges, maintaining genetic diversity, improving breeding strategies, combating inbreeding decline, and age determination. Therefore, future research on epigenetic resources is important for germplasm conservation, development, and utilization. This review proposes a new theoretical framework to elucidate the place of epigenetic resources in germplasm research and collects articles from the past 8 years that explore the inheritance of epigenetic information in aquatic animals. Integrating epigenetic research into germplasm studies enhances our understanding of population dynamics, adaptation, and evolutionary processes, thereby informing conservation strategies and enhancing aquaculture practices. By considering both genetic and epigenetic resources, we can address the challenges facing germplasm diversity and sustainable aquaculture more comprehensively.

Metagenomics reveals soil nitrogen cycling after vegetation restoration: Influence of different vegetation restoration strategies - Hengkang Xu; Chao Chen; Wenqing Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Applied Soil Ecology, 2024)

Soil particulate organic carbon regulates microbial carbon use efficiency in subtropical forests under nitrogen addition in different seasons - Xueqi Sun; Hao Sun; Qiufang Zhang; Biao Zhu; Hui Dai; Quanxin Zeng; Jingqi Chen; Wenwei Chen; Yuehmin Chen (Applied Soil Ecology, 2024)

Effects of temperature regime and food supply on asexual reproduction in Cyanea nozakii and Nemopilema nomurai - Song Feng; Guang-Tao Zhang; Song Sun; Fang Zhang; Shi-Wei Wang; Meng-Tan Liu (Hydrobiologia, 2015)

Breeding places, population dynamics, and distribution of the giant jellyfish Nemopilema nomurai (Scyphozoa: Rhizostomeae) in the Yellow Sea and the East China Sea - Song Sun; Fang Zhang; Chaolun Li; Shiwei Wang; Minxiao Wang; Zhencheng Tao; Yantao Wang; Guangtao Zhang; Xiaoxia Sun (Hydrobiologia, 2015)

Effects of duration at low temperature on asexual reproduction in polyps of the scyphozoan Nemopilema nomurai (Scyphozoa: Rhizostomeae) - Song Feng; Fang Zhang; Song Sun; Shiwei Wang; Chaolun Li (Hydrobiologia, 2015)

Effect of temperature and food type on asexual reproduction in Aurelia sp.1 polyps - Yan-Tao Wang; Shan Zheng; Song Sun; Fang Zhang (Hydrobiologia, 2015)